The Study of the Effects of Learning Management Using Baamboozle Games on Spelling Ability and Work Perseverance of Grade 4 Students - ถูระวรณ์ วรรณกร; แพทย์คดี วิษณุ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aimed to: (1) examine the spelling ability of Grade 4 students after undergoing learning activities using the Baamboozle games, based on a 60 percent criterion; and (2) develop the desirable characteristic of work perseverance among Grade 4 students after undergoing learning activities using the Baamboozle games. The target group consisted of seven Grade 4 students from Wat Metarang School. The research instruments included: (1) learning management plans incorporating the Baamboozle games, (2) a spelling ability test, and (3) a desirable characteristic assessment form. Data were analyzed using percentages, means, and standard deviations. The research findings revealed that: (1) the students’ spelling ability after undergoing learning activities using the Baamboozle games was 70.71 percent, which exceeded the set criterion of 60 percent; and (2) the students’ desirable characteristic of work perseverance was at a good level, with a mean score of 2.07 and a standard deviation of 0.83.